Financial Inclusion in India Through Pradhan Mantri Jan Dhan Yojana : An Empirical Analysis of Statistical Evidence - Tripathi, Ravindra; Yadav, Nikhil; Shastri, Rajesh Kumar (Indian Journal of Finance, 2016)
Pradhan Mantri Jan Dhan Yojana (PMJDY) is one of the remarkable steps taken by the present Government of India towards financial inclusion. Through this policy, Reserve Bank of India relaxed banks’ KYC norms and also extended zero balance facility along with accidental insurance facility on opening the saving bank account. However, merely opening the bank account is not effective financial inclusion unless a customer becomes financially literate and starts using different financial instruments like deposits or credit facility regularly. The aim of this study was to firstly investigate the spread of bank branches with respect to credit and deposits. Secondly, the study aimed toÂ identify responsible factors leading to significant changes in deposits and credit disbursement, and thirdly, the study explored the efforts taken by banks for spreading financial literacy. Regression analysis model and Pair t - test were adopted to analyze the effectiveness of bank branches and interview responses of bank managers were also analyzed to ascertain the qualitative efforts made by banks for spreading financial literacy. After analysis, it was found that after implementation of the policy, the credit disbursement by banks and deposits in banks increased. The number of zero balance bank accounts opened in PMDJY, and the low efforts made by banks for spreading financial literacy are threats for this scheme and for increasing financial inclusion in India, which need to be taken care of at policy levels.